UJI ANTAGONIS BEBERAPA ISOLAT PSEUDOMONAD FLUORESEN TERHADAP BAKTERI Ralstonia solanacearum PENYEBAB PENYAKIT LAYU TANAMAN NILAM SECARA IN VITRO - -, Nursati - (Pendidikan Biologi, 2014)
Nilam plant (Pogestomon Cablin Benth) is one of plant result atsiri oil that is important thing of cosmetics industry. Nilam plant has advantages like: difficult steam is better than eteris oil others, impediment wash, can be dissolved into alcohol and can blend with eteris oil others. One of causing Nilam Shrivel Plant Disease is offensive of Ralstonia Solanacearum. The purpose of the research is to know antagonist exam of some isolat Pseudomonad Fluoresen toward bacteria of ralstonia solanacearum caused nilam shrivel plant disease with in vitro.The research is done from April 2013 â October 2014, placed in Plant Physiology laboratory, FMIPA, UNP. This research use RAL with 5 steps and 5 exams. The ways are PfPj1, PfPj2, PfPj3, Cas3 and Kd7. The result is analyzed by using ANOVA in real fact 5% and if it is different that is continued with t exam DNMRT in real fact.The analysis result of many isolat Pseudomonad Fluoresen able stunts Ralstonia Solanacearum. Zone diameter is PfPj1 11.41, PfPj2 9.97, PfPj3 12.56, Cas3 11.25 and Kd7 10.26 isolat which have high inhibit zone PfPj3 12.56. in briefly, Pseudomonad Fluoresen able stunts Ralstonia Solanacearum development which is caused nilam shrivel plant disease with in vitro.